Pengembangan Guru Kreatif dan Inovatif dalam Meningkatkan Mutu Peserta Didik Pada Mata Pendidikan Agama Islam di SMP Muhammadiyah Parepare - Andi Abd Muis; Salmiati Salmiati; Andi Fitriani Djollong; Muh Aripail; Arham Arham (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
This research discusses the influence of Creative and Innovative Teachers in Improving the Quality of Learners in Subjects at Muhammadiyah Parepare Junior High School. The purpose of the research is to find out (1) Creative and innovative Teacher Criteria (2) How the Role of Creative and Innovative Teachers in Improving the Quality of Learners (3) How the Influence of Creative and Innovative Teachers on the improvement of Students in Muhammadiyah Parepare Junior High School. . This research uses a holistic approach that is a pedagogical approach. This type of research uses quantitative descriptive analysis methods. The method of data collection is carried out by observation methods, questionnaires, documentation and interviews. The analytical techniques used are descriptive techniques and inferential analysis. (2) With the management of the learning process program, improving the quality of learning carried out by educators can improve the quality of learners in Islamic Religious Education Subjects (3) Creative and Innovative Teachers in their development can provide a significant influence and contribute to improving the quality of learners in Muhammadiyah Parepare Junior High School. Based on the results of the study, the implications of the study were presented to the school to increase the role of educators in applying Creative and Innovative learning which includes the use of various techniques, ways and methods in learning.